2021
DOI: 10.1002/aenm.202101404
|View full text |Cite
|
Sign up to set email alerts
|

Stepping Out of Transition Metals: Activating the Dual Atomic Catalyst through Main Group Elements

Abstract: In recent years, investigations into atomic catalysts has accelerated significantly. Although different atomic catalysts have been developed, the introduction of main group elements is rarely considered. In this work, the possibility of introducing alkaline/alkaline earth metals (AAEM), post‐transition metal (Post‐TM), and metalloids to form stable graphdiyne‐based dual atomic catalysts (GDY‐DAC) is revealed. The main group elements not only act as a promising separator to improve the loading of DACs but also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 61 publications
0
29
1
Order By: Relevance
“…Furthermore, as a powerful tool, the machine learning (ML) technique has been introduced to predict the thermodynamic properties of electrocatalysts. [53][54][55] In this work, we have applied the Gaussian Process Regression (GPR) algorithm, which is able to obtain predictions based on a few parameters. Such methods are highly useful for the relatively smaller datasets in our work when compared with many state-of-the-art machine learning models.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, as a powerful tool, the machine learning (ML) technique has been introduced to predict the thermodynamic properties of electrocatalysts. [53][54][55] In this work, we have applied the Gaussian Process Regression (GPR) algorithm, which is able to obtain predictions based on a few parameters. Such methods are highly useful for the relatively smaller datasets in our work when compared with many state-of-the-art machine learning models.…”
Section: Resultsmentioning
confidence: 99%
“…The increased deviations of the predictions suggest that the electronic structures cannot be fully revealed by the physicochemical properties. Recently, they have further extended the research from transition metal and lanthanide metals to the main group elements 126 . Based on the similar GPR method, they have identified that the involvements of s and p orbitals have evidently perturbed the prediction accuracies of both formation energies and p‐band center, especially the alkaline/alkaline earth metals, which show much higher RMSE than other groups (Figure 11G–I).…”
Section: The Application Of ML In Materials Sciencementioning
confidence: 97%
“…Copyright 2021 Wiley‐VCH). The comparison of the GPR model predicted data and original data of the formation energy in (G) alkaline/alkaline earth metals based GDY‐DAC, (H) post‐transition metals based GDY‐DAC and (I) metalloid based GDY‐DAC (Reproduced with permission 126 . Copyright 2021 Wiley‐VCH)…”
Section: The Application Of ML In Materials Sciencementioning
confidence: 99%
“…They further experimented with verifying that a Zn/Ln DMS catalyst was highly effective for ECR to produce CO/H 2 syngas with a tunable ratio 159 . In addition, using the same machine learning techniques, they also discover that combining main group elements with TM and Ln metals is able to form the stable graphdiyne‐based DMS with high electroactivity 161 …”
Section: Strategies For Optimization Of Ldm Supported Sacs For Ecrmentioning
confidence: 99%
“…159 In addition, using the same machine learning techniques, they also discover that combining main group elements with TM and Ln metals is able to form the stable graphdiyne-based DMS with high electroactivity. 161…”
Section: Designing Dual-metal Sitementioning
confidence: 99%